The impact of psychiatric and medical comorbidity on the risk of mortality: a population-based analysis. Issue 2 (28th January 2021) - Davies, Simon J. C.; Iwajomo, Tomisin; de Oliveira, Claire; Versloot, Judith; Reid, Robert J.; Kurdyak, Paul
Abstract: Background: As life expectancy increases, more people have chronic psychiatric and medical health disorders. Comorbidity may increase the risk of premature mortality, an important challenge for health service delivery. Methods: Population-based cohort study in Ontario, Canada of all 11 246 910 residents aged ⩾16 and <105 on 1 April 2012 and alive on 31 March 2014. Secondary analyses included subjects having common medical disorders in 10 separate cohorts. Exposures were psychiatric morbidity categories identified using aggregated diagnosis groups (ADGs) from Johns Hopkins Adjusted Clinical Groups software ® (v10.0); ADG 25: Persistent/Recurrent unstable conditions; e.g. acute schizophrenic episode, major depressive disorder (recurrent episode), ADG 24: Persistent/Recurrent stable conditions; e.g. depressive disorder, paranoid personality disorder, ADG 23: Time-limited/minor conditions; e.g. adjustment reaction with brief depressive reaction. The outcome was all-cause mortality (April 2014–March 2016). Results: Over 2 years' follow-up, there were 188 014 deaths (1.7%). ADG 25 conferred an almost threefold excess mortality after adjustment compared to having no psychiatric morbidity [adjusted hazard ratio 2.94 (95% CI 2.91–2.98, p < 0.0001)]. Adjusted hazard ratios for ADG 24 and ADG 23 were 1.12 (95% CI 1.11–1.14, p < 0.0001) and 1.31 (95% CI 1.26–1.36, p < 0.0001). In all 10 medical disorder cohorts, ADG 25 carried significantly greater mortality risk compared to no psychiatric comorbidity. Conclusions: Psychiatric disorders, particularly those graded persistent/recurrent and unstable, were associated with excess mortality in the whole population, and in the medical disorder cohorts examined. Future research should examine whether service design accounting for psychiatric disorder comorbidity improves outcomes across the spectrum of medical disorders.